KOTA CALANG PASCA TSUNAMI (Satu Tinjauan Perkembangan Infrastruktur Tahun 2005-2017) - Chandra Seba; Mawardi ,; Anwar Yoesoef (Universitas Syiah Kuala, 2017)
ABSTRACKStudy of the history of the city is still minimaly considered in the province of Aceh. One of them is Calang city which is capital distrik of Aceh Jaya. Calang city was founded in 2002 along with the establishment of the district. After the tsunami of 2004, this city began to develop in various infrastructure, especially economic infrastructure, government and infrastructure for the benefit of the general public.The research is titled, “Calang City After The Tsunami (An Infrastructure Development Review, 2005-2017)”, aims to (1) reconstruct infrastructure development of Calang city after tsunami, and (2) to analyze the factors that influence the development of Calang city infrastructure after the tsunami, 2005-2017.This research uses qualitative approach and historical method, which has a theme selection step, heuristics, verification, interpretation and historiography. Technique of data collecting is done by interview, documentation, liblary research and observation. Based on the results of the research, it is known that (1) the development of Calang City infrastructure since 2005-2017 continues to increase to a more advanced direction. It is characterized by the increasing of road transport infrastructure, health/sinetasi, education, offices, houses of worship, industry, market, company, restaurant , SME facilities and electricity infrastructure, and (2) the development of infrastructure of Calang is influenced by the state of nature, the ecology of the city as well as government support and funding from abroad. Keywords :Progress, Infrastructure, Calang City. ABSTRAK Kajian sejarah kota merupakan kajian yang masih minim diperhatikan di Provinsi Aceh. Salah satunya ialah Kota Calang yang merupakan ibukota dari Kabupaten Aceh Jaya. Kota ini berdiri tahun 2002 berbarengan dengan berdirinya kabupaten tersebut. Pasca tsunami 2004, kota ini terlihat mulai berkembangnya berbagai infrastruktur baik infrastruktur ekonomi, pemerintahan dan infrastruktur untuk kepentingan masyarakat umum.Penelitian yang berjudul “Kota Calang Pasca Tsunami, (Satu Tinjauan Perkembangan Infrastruktur, 2005-2017)”, bertujuan untuk(1) merekontruksi kembali perkembangan infrastruktur kota Calang pasca tsunami, 2005-2017 dan (2) menganalisis faktor-faktor yang mempengaruhi perkembangan infrastruktur kota Calang pasca tsunami, 2005-2017.Penelitian ini menggunakan pendekatan kualitatif dan metode sejarah, yang memiliki langkah pemilihan tema, heuristik, verifikasi, interpretasi dan historiografi. Teknik pengumpulan data dilakukan dengan wawancara, dokumentasi, studi pustaka dan observasi.Berdasarkan hasil penelitian diketahui bahwa (1) perkembangan infrastruktur Kota Calang sejak 2005-2017 terus mengalami kenaikan ke arah yang lebih maju. Hal ini ditandai dengan semakin bertambahnya infrastruktur transportasi jalan, kesehatan/sinetasi, pendidikan, perkantoran, rumah ibadah, industri, pasar, perusahaan, restoran/rumah makan, fasilitas UKM dan infrastruktur listrik, dan (2) perkembangan infrastrukur Kota Calang ini dipengaruhi oleh keadaan alam, ekologi kota serta dukungan pemerintah dan bantuan dana dari luar negeri. Kata Kunci:Perkembangan, Infrastruktur, Kota Calang.